Kecurangan UTBK dalam Bingkai Media: Analisi Wacana Kritis Model Nurman Fairclough pada Pemberitaan Online CNN Indonesia - Subiyakti, Evi Titin; Asrofah, Asrofah (UIR Press, 2025)
Online media play a significant role in shaping public perceptions of educational issues, including cases of cheating in the UTBK national entrance examination. Although previous studies have widely applied Fairclough’s Critical Discourse Analysis (CDA), many still emphasize linguistic features without fully integrating the dimensions of discursive practice and social practice. This study aims to examine how CNN Indonesia constructs the issue of UTBK cheating in the news article titled Kecurangan UTBK Makin Canggih, Peserta Pasang Kamera di Kacamata by employing Fairclough’s three dimensional framework. Using a qualitative approach, the analysis focuses on textual features, the processes of discourse production and distribution, and the broader sociocultural context. The findings indicate that the report highlights the number of offenders, the sophistication of cheating technologies, and indications of insider involvement to portray the issue as serious and systemic. The discursive practice dimension reveals the dominance of a single authoritative source and a narrative structure that progresses from factual reporting to moral reinforcement. At the social practice level, the news connects cheating with broader societal values such as trust and integrity in the education system. Overall, the study demonstrates that media discourse not only conveys information but also shapes public understanding by framing educational issues as moral and institutional concerns.